"Helix‐in‐Helix" Superstructure Formation through Encapsulation of Fullerene‐Bound Helical Peptides within a Helical Poly(methyl methacrylate) Cavity. (21st December 2016) - Ousaka, Naoki; Mamiya, Fumihiko; Iwata, Yoshiaki; Nishimura, Katsuyuki; Yashima, Eiji
Abstract: A one‐handed 310 ‐helical hexapeptide is efficiently encapsulated within the helical cavity of st‐PMMA when a fullerene (C60 ) derivative is introduced at the C‐terminal end of the peptide. The encapsulation is accompanied by induction of a preferred‐handed helical conformation in the st‐PMMA backbone with the same‐handedness as that of the hexapeptide to form a crystalline st‐PMMA/peptide‐C60 inclusion complex with a unique optically active helix‐in‐helix structure. Although the st‐PMMA is unable to encapsulate the 310 ‐helical peptide without the terminal C60 unit, the helical hollow space of the st‐PMMA is almost filled by the C60 ‐bound peptides. This result suggests that the C60 moiety can serve as a versatile molecular carrier of specific molecules and polymers in the helical cavity of the st‐PMMA for the formation of an inclusion complex, thus producing unique supramolecular soft materials that cannot be prepared by other methods. Abstract : Links‐ und Rechtsgewinde : Chirale helikale Peptide, die am einen Ende ein C60 ‐Molekül tragen, werden durch die starken Wechselwirkungen des C60 in der helikalen Kavität von syndiotaktischem Poly(methylmethacrylat) (st‐PMMA) eingeschlossen. Die Verkapselung bewirkt, dass das st‐PMMA‐Rückgrat die gleiche Händigkeit wie die eingeschlossenen Peptide annimmt.